PENCARIAN CITRA BERBASIS PENGENALAN WAJAH UNTUK ABSENSI MENGAJAR DOSEN IBI DARMAJAYA - setyawan, dodi; Arkhiansyah, Yuni (IIB Darmajaya, 2011)
This research will build a system or tool (software) for face recognition based image search for lecturers to teach IBI Darmajaya attendance. This study used the face with a normal pose or face with position perpendicular to the face. Facial image recognition method using the 2D-DCT (Discrete Cosine Transform Dimention 2) good image and image database query. The system is expected to replace the old model of teaching faculty attendance Darmajaya IBI. Lecturers who will teach come to PLPP no longer need to put or write down the number of meetings, day and date, subject and sub ââsubject but the teacher just came in front of the camera PLPP automatic scanner and a professor of facial images will be taken then processed by the program, the program will inform the faculty meeting and room number. Effectiveness of business processes, learning and human resource efficiency will be achieved Keywords: Absenteeism, Face Recognition, 2D-DCT